Evaluation of the Effectiveness of the Policy for the Repatriation of Foreign Assets into the Country in the Voluntary Disclosure Program - Gultom, Harry Gregorius; Rahayu, Ning (Universitas Teuku Umar, 2023)
This research will analyze the effectiveness of the policy of repatriating foreign assets into the country in the Voluntary Disclosure Program. Researchers used the 7's framework proposed by McKinsey consultants with the elements of shared values, staff, system, structure, strategy, skills, and style in assessing the effectiveness of asset repatriation. This research aims to determine whether the repatriation of assets in the Voluntary Disclosure Program has been effective and the inhibiting factors in carrying out asset repatriation by the Directorate General of Taxes. This research uses a post-positivist approach with a descriptive research type. Data collection techniques were obtained through literature studies and field studies. Field studies were conducted using in-depth interviews with relevant stakeholders such as the Directorate General of Taxes, Academics, the House of Representatives, and Practitioners. The research results show that the elements of shared values, structure, and style are practical, but the elements of strategy, skills, staff, and systems could be more. There are also obstacles faced by the Directorate General of Taxes, namely policies implemented at the wrong time due to the COVID-19 pandemic, taxpayer assets that are not liquid plus the shadow of a global recession due to the pandemic, programs that are less attractive to taxpayers, lack of legal certainty, regarding the Voluntary Disclosure Program policy, as well as the unstable economic and political conditions in Indonesia due to the pandemic.